2017
DOI: 10.1007/s10654-017-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between smoking and HLA genes in multiple sclerosis: replication and refinement

Abstract: Interactions between environment and genetics may contribute to multiple sclerosis (MS) development. We investigated whether the previously observed interaction between smoking and HLA genotype in the Swedish population could be replicated, refined and extended to include other populations. We used six independent case–control studies from five different countries (Sweden, Denmark, Norway, Serbia, United States). A pooled analysis was performed for replication of previous observations (7190 cases, 8876 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 39 publications
2
61
1
1
Order By: Relevance
“…These studies have been limited to HLA genes so far, with positive results reported for active and passive smoking, EBV infection and infectious mononucleosis, and childhood/adolescent obesity [reviewed in [5]]. For example, in a pooled analysis of six datasets, smokers carrying HLA-DRB1*15 and lacking HLA-A*02 had a 13-fold increased disease risk compared with never smokers without these genetic risk factors (OR 12.7, 95% CI 10.8–14.9) [69]. Novel modeling approaches will afford the analysis of gene-environment interactions genome-wide [70], potentially addressing an important knowledge gap in the understanding of MS heritability.…”
Section: Gene Environment Interactions In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been limited to HLA genes so far, with positive results reported for active and passive smoking, EBV infection and infectious mononucleosis, and childhood/adolescent obesity [reviewed in [5]]. For example, in a pooled analysis of six datasets, smokers carrying HLA-DRB1*15 and lacking HLA-A*02 had a 13-fold increased disease risk compared with never smokers without these genetic risk factors (OR 12.7, 95% CI 10.8–14.9) [69]. Novel modeling approaches will afford the analysis of gene-environment interactions genome-wide [70], potentially addressing an important knowledge gap in the understanding of MS heritability.…”
Section: Gene Environment Interactions In Msmentioning
confidence: 99%
“…Emerging evidence suggests that while some risk loci are conserved, ethnic-specific variants may contribute to shaping disease susceptibility in different populations (50, 6972). …”
Section: Figmentioning
confidence: 99%
“…In rheumatoid arthritis, the risk of developing antibodies to citrullinated proteins has been associated with gene–environment interactions between HLA‐DRB1 shared epitope alleles and smoking . Other diseases showing associations between HLA and smoking include idiopathic inflammatory myopathies, Parkinson disease, multiple sclerosis, and lymphoma …”
Section: Discussionmentioning
confidence: 99%
“…30 In rheumatoid arthritis, the risk of developing antibodies to citrullinated proteins has been associated with gene-environment interactions between HLA-DRB1 shared epitope alleles and smoking. [30][31][32][33][34] Other diseases showing associations between HLA and smoking include idiopathic inflammatory myopathies, 35 Parkinson disease, 36,37 multiple sclerosis, [38][39][40][41] and lymphoma. 42 In the current study, the strong effects of HLA-DRB1*15:02 on the risk of UC were observed in never smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The additive odds measures of joint effects and interaction are defined in Section 3, and the procedures for estimating them are given in Section 4. Our methodology is illustrated in Section 5 for a multiple sclerosis (MS) dataset from Hedström et al [14], and a concluding discussion appears in Section 6.…”
Section: Introductionmentioning
confidence: 99%